2015
DOI: 10.1590/s1677-5538.ibju.2014.0195
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of female overactive bladder using urodynamics: relationship with female voiding dysfunction

Abstract: Purpose:To investigate the role of urodynamic study (UDS) in female patients with overactive bladder (OAB) analyzing the relationship between OAB symptoms and female voiding dysfunction (FVD).Materials and Methods:We analyzed the clinical and urodynamic data of 163 women with OAB symptoms. OAB symptoms were categorized as dry and wet. FVD was described as detrusor underactivity (DUA), which was defined as a maximum flow rate (Qmax) of ≤15mL/s associated with a detrusor pressure at Qmax (PdetQmax) of ≤20cmH2O, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 25 publications
(27 reference statements)
2
23
0
Order By: Relevance
“…Our ndings showed a high prevalence of DO (69.68%) and abnormal voiding patterns (65.16%) among NP women with OAB as compared with parous women. Our nding of VD with an abnormal voiding pattern corroborates the ndings of Cho et al, who reported that more than half the women in their study presented with OAB symptoms in conjunction with VD, as revealed by UDS 8 . In addition, Nitti et al reported the existence of very high overlapping storage (79%) and obstructive symptoms (76%) in 331 non-neurogenic VD women who underwent multichannel video-UDS for non-neurogenic VD 17 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our ndings showed a high prevalence of DO (69.68%) and abnormal voiding patterns (65.16%) among NP women with OAB as compared with parous women. Our nding of VD with an abnormal voiding pattern corroborates the ndings of Cho et al, who reported that more than half the women in their study presented with OAB symptoms in conjunction with VD, as revealed by UDS 8 . In addition, Nitti et al reported the existence of very high overlapping storage (79%) and obstructive symptoms (76%) in 331 non-neurogenic VD women who underwent multichannel video-UDS for non-neurogenic VD 17 .…”
Section: Discussionsupporting
confidence: 92%
“…It is generally considered that detrusor overactivity (DO) plays a role in OAB, but not all OAB patients are diagnosed with DO after urodynamic study (UDS) 5,6 . In addition to DO, bladder outlet obstruction (BOO) may play a role in the development of OAB, because OAB and voiding dysfunction (VD) can coexist 7,8 . VD, which is de ned as abnormally slow and/or incomplete micturition, can be classi ed as BOO (mechanical and functional) and detrusor underactivity (DU) 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Digesu et al [39], in their study showed that only 27.5% of women with DO on UDS had OAB symptoms, whilst only 54% of women with OAB symptoms had DO on UDS, so they concluded that symptomatic diagnosis alone of OAB was not recommended for women with LUTS due to weak correlation between symptoms and UDS diagnosis. In another study, of the women with OAB symptoms, only 38.7% (63/163) had DO on UDS [38].…”
Section: Oabmentioning
confidence: 89%
“…Cho et al [38] investigated the role of UDS in female patients with OAB. Clinical and urodynamic data of 163 women with OAB were analysed.…”
Section: Oabmentioning
confidence: 99%
“…Cho et al [29] reported similar Qmax (mean: 15.3 mL/sec vs. 15.0 mL/sec, P=0.759) and PdetQmax (mean: 31.0 cm H 2 O vs. 31.4 cm H 2 O, P=0.862) between the OAB-dry and OAB-wet patients. In our study, high Qmax (OR, 1.06) and high PdetQmax (OR, 1.01) were identified as novel predictors for OAB-wet (Table 3).…”
Section: Discussionmentioning
confidence: 86%